Analisis Kekurangan Mahasiswa PPG dalam Jabatan dalam Membuat Video Pembelajaran Di LPTK Universitas Muhamadiyah Tapanuli Selatan - Rini Kesuma; Lisa Fitri Meidipa (CV. Alfa Pustaka, 2026)
One of the government's ways of improving the welfare of teachers is through the in-service PPG program, or what is called teacher certification in the end. Based on the Regulation of the Minister of Education, Culture, Research, and Technology Number 19 of 2024 concerning Professional Teacher Education, chapter I, article 1, Professional Teacher Education, hereinafter abbreviated as PPG, is an educational program held after an undergraduate or applied undergraduate program for prospective teachers or teachers to obtain an educator certificate (Minister of Education, 2024). which is attached to the LPTK of Universitas Muhammadiyah Tapanuli Selatan. With this PPG, it is a form of self-assessment for teachers to continue learning because after passing the PPG, students will get a new title called GR. This title shows that teachers must become more professional in carrying out teaching and learning activities.